Social spending and Income redistribution in Argentina during the 2000s: The rising role of noncontributory pensions - Nora Lustig; Carola Pessino (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2012)
Between 2003 and 2009, Argentina's social spending as a share of GDP increased by 7.6 percentage points. Marginal benefit incidence analysis for 2003, 2006, and 2009 suggests that the contribution of cash transfers to the reduction of disposable income inequality and poverty rose markedly between 2006 and 2009 primarily due to the launching of a noncontributory pension program - the pension moratorium - in 2004. Noncontributory pensions as a share of GDP rose by 2.2 percentage points between 2003 and 2009 and entailed a redistribution of income to the poor, and from the formal sector pensioners with above minimum pensions to the beneficiaries of the pension moratorium. The redistributive impact of the expansion of public spending on education and health was also sizeable and equalizing, but to a lesser degree. An assessment of fiscal funding sources puts the sustainability of the redistributive policies into question, unless nonsocial spending is significantly cut.
Keywords: D31; H22; I38; 330; social spending; benefit incidence; inequality; poverty; Argentina; Öffentliche Sozialausgaben; Einkommensverteilung; Armut; Argentinien